Nonverbal Communication and Cultural Features of Highest-grossing Movies among Asean Countries - Bautista, Ed (Universitas Jambi, Magister Program of English Education Department, 2023)
This paper analyzes the nonverbal communication and cultural features of the Highest-Grossing Movies Among Selected ASEAN Countries. There are two approaches used in this study. First, it sought to identify the nonverbal communication features through semiotic analysis of the most important movie scenes, and second, it determined the cultural features of the movies through a readers-oriented approach. Through the analysis of the cultural features, ASEAN nations such as the Philippines, Malaysia, and Thailand share the same values such as the strong family ties. Also, the belief in the supernatural and superstition is evident in the stories. The non-verbal communication features analysis established that all of these movies portrayed different signs or symbols that can be traced and interpreted as part of their culture or norm. Thus, culture plays a significant element among the selected highest-grossing ASEAN films.